Iztēli Rosinoša Apoloģētika. Pārdomas, Lasot S. Krēūmiņas-Koņkovas Monogrāfiju Sensus Divinitatis: Imaginative Apologetics. Some Thoughts on Reading S. Krūmiņa-Koņkova's Monograph "Sensus Divinitatis". - Vējš, Jānis Nameisis (Cel̜š, 2013)
The article attempts to draw parallels between some recent developments in the field of analytic theology in general and a book published in Latvia in 2013. The monograph "Sensus Divinitatis. Exercises in Philosophical Theology" by a Latvian scholar Solveiga Krumina-Konkova consists of two parts, one of which ("Evil and the Human Free Will") reproduces an earlier book of the same author published in different circumstances and reflecting the spiritual atmosphere of the dramatic societal changes in Latvia of two decades ago; the second part presents an overview of the whole problematics of theodicy on a much wider scale, by using a methodological approach, she designates as belles-lettres. Basically, the monograph is concerned with the analysis of the views of the well-known religious philosopher Alvin Plantinga. The originality of Krumina-Konkova's work consists in her attempt to interpret the teaching of Plantinga in an imaginative fashion, by making use of both analytical and phenomenological tools of expression. This has led the author of the present article to seek methodological parallels with the recently popular "imaginative apologetics" trend, as propounded in the work "Imaginative Apologetics. Theology, Philosophy and the Catholic Tradition" (2011), edited by Andrew Davison, with a foreword by John Milbank. The conception of the imaginative apologetics envisages a new turn in the apologetical strategy, whereby it is seen as a complex of "narrative, confession and imaginative witness by the human person in the name of divine personality against the impersonality of the city...". The author of the present article claims that the book "Sensus Divinitatis" corresponds to these standards, and proposes that imaginative apologetics is to be distinguished from the so-called devotional type of spiritual literature.